The oil industry in India : some economic aspects - Dasgupta, Biplab (London, Cass, 1971)
The book examined some major issues facing the oil industry of India.
Include bibliography and index
kjo 18/01/2019
Loans
Keywords: Petroleum industry; Petroleum industry and trade; Oil industry; India